Mechanical stretching-induced electron transfer reactions and conductance switching in single molecules - Li, Y.; Haworth, N.; Xiang, L.; Ciampi, Simone; Coote, M.; Tao, N. (American Chemical Society, 2017)
A central idea in electron-transfer theories is the coupling of the electronic state of a molecule to its structure. Here we show experimentally that fine changes to molecular structures by mechanically stretching a single metal complex molecule via changing the metal–ligand bond length can shift its electronic energy levels and predictably guide electron-transfer reactions, leading to the changes in redox state. We monitor the redox state of the molecule by tracking its characteristic conductance, determine the shift in the redox potential due to mechanical stretching of the metal–ligand bond, and perform model calculations to provide insights into the observations. The work reveals that a mechanical force can shift the redox potential of a molecule, change its redox state, and thus allow the manipulation of single molecule conductance.